Investigation on SMEs Features in Both China and Iran - Loroun, Babak Besharati; Ming, Xu; Ali, Syed Ahtsham (International Journal of Business, Economics and Management, 2018)
In this article the Chinese and Iranian SMEs features have been investigated and briefly pointed out some common features and differences. Comparable table has been developed. It is also mentioned that how the Chinese entities started the low price strategies to capture the foreign markets. It has been discussed that how SMEs of China could overcome the challenges and barriers they have encountered. But recently Chinese companies have lot of advantages to go to the market with low price strategy due the elements which influences their cost to be low is getting expensive. On the other side, SMEs of Iran are more risk taker and also interested to be more active in international markets. But due to the lack of interest to develop their initial relationship with overseas companies, political risks, sanctions, lack of banking and finance support of government, fluctuation of exchange rate occurs. So they are not so successful in entering the foreign markets despite of their suitable capacities and possibilities. Chinese SMEs are more cautious and playing a role in stable economic and political environment and having also better access to the market intelligence, fund and wide range of business services render by different providers. By studying the feature of SMEs in both countries we will have a better study on similarity and differences and we will find out the effect of any specific feature in business cooperation of two sides. It could be also helpful how to identify and recognize the ways and methods to make SMEs of two countries to be closer to each other and maintain the stable economic and commercial ties between two nations.